تقويم أهمية الفحص الخلوي للرشافة بالإبرة الرفيعة في تشخيص آفات الثدي - قنجراوي, أكثم; الشهابي, زهير; غانم, حسان (Latakia University Journal -Medical Sciences Series, 2019)
أجري الفحص الخلوي للرشافة بالإبرة الرفيعة (FNAC )لِ 60 مريض ومريضة من المقبولين في قسم الجراحة أو المراجعين للعيادة الجراحي, حيث كانت نسبة النساء 96.7 % والرجال3.3 % وكانت النسبة الكبرى من النساء وحالتي الرجال في العقد الثالث من العمر. عدد الحالات الثنائية الجانب 3 حالات بنسبة 5% وأحادية الجانب 95 %, الجهة المسيطرة هي ا ليسرى بنسبة 60 % واليمنى 35 % . الشكاية الرئيسية توزعت مابين كتلة الثدي 76.66 % ومن ثم ألم الثدي بنسبة 16.66 % ونز من الحلمة بنسبة 6.66 % أعلى نسبة للإصابة كانت متوضعة في الربع العلوي الوحشي بنسبة 46.67 %. أجري التصوير الشعاعي بالأمواج فوق الصوتية في 30 حالة كانت السلبية الكاذبة 6.66 % والإيجابية الكاذبة 13.33%, وكانت الحساسية 83.4 % والنوعية 77.7% . أجري التصوير الشعاعي للثدي في 28 حالة كانت السلبية الكاذبة10.72 % والإيجابية الكاذبة 10.72% الحساسية 76.9 % والنوعية 80 % . أجري الفحص الخلوي للرشافة بالإبرة الرفيعة FNAC لكامل مرضى عينة الدراسة فكانت السلبية الكاذبة 3.33 % والإيجابية الكاذبة 1.66 %, الحساسية 95.78 % والنوعية 92.33 % . القدرة التشخيصية كانت عالية ل FNAC في الورم الليفي والداء الليفي الكيسي وفي التوجه نحو تشخيص السرطانات, وكانت أقل فعالية في تشخيص الأورام الغدية . بمقارنة FNAC مع التصوير بالأمواج فوق الصوتية والتصوير لشعاعي للثدي وجدنا أن FNAC هو الأعلى بالحساسية والنوعية. مضاعفات FNAC : النزف بنسبة 3.33 %, الخمج بنسبة 1.66 %,العينة الخاطئة بنسبة 3.33 %, أذية القناة اللبنية 1.66 %. تراجعت المضاعفات ً بالعلاج المحافظ. The Fine Needle Aspiration Cytology (FNAC) was performed to sixty patients who were admitted to the surgical department or surgical clinic of AL-Assad Hospital in Lattakia. The percentage of women in the study group student was 96,7% and men 3,3%. The peak incidence of the both men and women was in the third decade. The bilateral cases were found in 3 patients 5% ,and the unilateral lesions were in 57 patients with percentage of 95% .The left side was dominant in 60% .and right side in35%. The main complaint was the breast mass with a rate of 76,66% ,the breast pain in 16,66 %, the nipple discharge in 6.6 % .Most of the lesions located in lateral superior quarter in 46,67% of all cases. The ultrasound (ECHO) was done to 30 patients ,the false negative cases were 6,6 %, false positive cases were 13,33%, sensitivity was 83,4% ,and specificity was 77,7%. The mammography was done to 28 patients, the false negative cases were 10,72%, false positive cases were 10,7%, sensitivity was 76,9% ,and specificity was 80%. FNAC was done to all patients, the false negative cases were 3,33%, false positive cases were 1,66%, sensitivity was 95,78% ,and specificity was 92,33%. The diagnostic accuracy of FNAC was high in Fibroma, Fibrocystic disease, it was of high efficiency in orienting the diagnosis of Malignancy, and it was less effective in diagnosing of Adenoma. We found out that FNAC had the highest sensitivity and specificity compared with ECHO and Mammography. The FNAC complications were: Hemorrhage 3,33% ,Infection 1,66%, Missed Specimen 3,33%, and Injury of Mammary Duct 1,66%. The complications cured by conservative management